External auditory canal stenosis due to isolated fibrous dysplasia of temporal bone: a case report - Silu, Manju; Gupta, Gaurav (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Benign disease of bone marrow in which marrow is reorganize into fibrous tissue and immature woven bone, is known as fibrous dysplasia. Involvement of temporal bone is rare and can be isolated or in monostotic or polystotic form with various otologic manifestations. We are here reporting a case of fibrous dysplasia of the unilateral temporal bone who presented with hearing loss and stenosis of the external auditory canal. External auditory canal stenosis due to fibrous dysplasia was managed with canalplasty and patient was free of recurrence till last follow up. Fibrous dysplasia of isolated temporal bone is a rare entity which requires high grade of suspicion in a patient who presents with unusual bony swellings in the ear. Its management usually includes resection of the most affected part of temporal bone in order to achieve auditory canal patency and restoration of hearing. After surgery, a close follow up is warranted due to its propensity of recurrence.